CSR Moderation Effects on the Influence of Capital Structure, Dividend Policy, Profitability on Firm Value (Studies on Food and Beverage Companies in Indonesia, Malaysia and Singapore in 2019-2021): Studies on Food and Beverage Companies in Indonesia, Malaysia and Singapore in 2019-2021 - Christine Benedicta Sutanto; Sugeng Hariadi (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of capital structure, dividend policy and profitability on firm value with corporate social responsibility as a moderating variable. The sample for this research are food and beverage companies listed on the Indonesia Stock Exchange, Malaysia Stock Exchange and Singapore Stock Exchange in 2019-2021. Samples were taken using purposive sampling method and 108 samples were obtained. Data analysis used is descriptive statistics, R-square and path coefficient, with data processing using SmartPLS 4. The results show that capital structure, dividend policy and profitability have a significant effect on firm value. Meanwhile, social responsibility is not able to moderate the effect of capital structure, dividend policy and profitability on firm value.